Study on main controlling factors of high injection pressure in offshore heavy oil reservoir. (January 2019) - Wang, Yu; Zhang, Hong; Zhu, Shijie; Zhao, Wensen; Shi, Leiting
Abstract: High injection pressure, insufficient steam injection rate and low bottom hole dryness seriously affect the application effect of steam stimulation in offshore heavy oil reservoir. By analyzing the factors affecting the reservoir conditions of high injection pressure during huff and puff, it can be concluded that the oil viscosity increases and the permeability decreases. The grey correlation analysis shows that the contribution of unit viscosity increase to injection pressure increase is twice that of unit permeability decrease. In view of the main controlling factors, the viscosity change of crude oil was studied indoors. The results showed that: 1) The content of heavy crude oil increased, and the viscosity of crude oil increased linearly; 2) The reverse phase point of oil emulsification at reservoir temperature is 50% water cut, and the viscosity of oil-in-water emulsion will increase with the increase of water cut; 3) the higher the viscosity of asphaltene is, the stronger the viscosity is. According to the actual situation of offshore heavy oilfield, residue of heavy components and emulsification of oil-in-water is the main factor affecting steam injection.